Studying Dopa Adhesion on Polystyrene Under Water - Yıldız, Remziye; Yıldız, Remziye; Akdoğan, Yaşar; Emrullahoğlu, Mustafa (Izmir Institute of Technology, 2021)
Mussels wet adhesive performance has been arousing curiosity for a long time. It is found that 3,4-dihydroxyphenylalanine (DOPA) is responsible for adhesive properties of mussels. Despite a large body of research characterizing the interactions DOPA with hydrophilic surfaces, relatively few works have addressed the mechanism of interactions with hydrophobic surfaces. The benzene ring of DOPA is the main attributor to the adhesion on hydrophobic polystyrene (PS) surface. However, here we showed that two hydroxyl groups of catechol have also effects on wet adhesion. We studied wet adhesive properties of DOPA, tyrosine and phenylalanine functionalized PEG polymers, PEG-(N-Boc-L-DOPA)4, PEG-(N-Boc-L-Tyrosine)4, PEG-(N-Boc-L-Phenylalanine)4, on spin labeled PS nanobeads (SL-PS) by electron paramagnetic resonance (EPR) spectroscopy. Surface coverage ratio of SL-PS upon additions of PEG-(N-Boc-L-DOPA)4, PEG-(N-Boc-L-Tyrosine)4 and PEG-(N-Boc-L-Phenylalanine)4 showed that SL-PS was covered with 70%, 50% and 0%, respectively. This showed that spontaneous wet adhesion on PS increases with the number of amino acids hydroxyl groups. This is also supported with the density functional theory (DFT) energy calculations and ab-initio molecular dynamics (AIMD) simulations. In water, interactions between water molecules and hydroxyl groups on the catechol induce catechol adhesion via π-π stacking between the catechol and double styrene rings which were already tilted out with water.

Midyenin ıslak yapışkanlık performansı uzun zamandır merak uyandırmaktadır. Midyelerin yapışkan özelliklerinden 3,4-dihidroksifenilalaninin (DOPA) sorumlu olduğu bulunmuştur. DOPA'nın hidrofilik yüzeylerle etkileşimlerini karakterize eden araştırmalar bulunmasına rağmen, nispeten az sayıda çalışma hidrofobik yüzeylerle olan etkileşim mekanizmasına değinmiştir. DOPA'nın benzen halkası, hidrofobik polistiren (PS) yüzey üzerindeki yapışmaya ana katkı sağlar. Bununla birlikte, burada iki hidroksil katekol grubunun da ıslak yapışma üzerinde etkileri olduğunu gösterdik. Elektron paramanyetik rezonans (EPR) spektroskopisi ile spin etiketli PS nano tanecik (SL-PS) üzerinde DOPA, tirozin ve fenilalanin ile işlevselleştirilmiş PEG polimerlerinin, PEG-(N-Boc-L-DOPA)4, PEG-(N-Boc-L-Tirozin)4, PEG-(N-Boc-L-Fenilalanin)4, ıslak yapışkan özelliklerini inceledik. PEG-(N-Boc-L-DOPA)4, PEG-(N-Boc-L-Tirozin)4 ve PEG-(N-Boc-L-Fenilalanin)4 eklenmesi ile SL-PS'nin yüzey kaplanma oranı sırasıyla %70, %50 ve %0 olarak bulunmuştur. Bu, PS üzerindeki kendiliğinden gerçekleşen ıslak yapışmanın amino asit hidroksil gruplarının sayısı ile arttığını göstermiştir. Elde edilen sonuçlar yoğunluk fonksiyonel teorisi (DFT) enerji hesaplamaları ve ab-initio moleküler dinamik (AIMD) simülasyonları ile de desteklenmiştir. Su içerisinde, su molekülleri ve katekol üzerindeki hidroksil grupları arasındaki etkileşimler, katekol ve halihazırda suyla eğilmiş olan çift stiren halkaları arasındaki π-π yığılması yoluyla katekol yapışmasına neden olmaktadır.
Dopa'nın Su İçerisinde Polistirene Yapışma Çalışması
Thesis (Master)--Izmir Institute of Technology, Materials Science and Engineering, Izmir, 2021
Includes bibliographical references (leaves. 52-57)
Text in English; Abstract: Turkish and English
Keywords: DOPA; Polystyrene; Mussel foot proteins; Hydroxyl groups